Efficacy of dexamethasone intravitreal implant combined with anti-VEGF drugs in the treatment of diabetic macular edema: a systematic review and meta-analysis - Chen, Fang; Wang, Xiaoqin; Chen, Ming; Xin, Mei; Xian, Yiping (Frontiers in Endocrinology, 2026)
BackgroundDiabetic macular edema (DME) remains a leading cause of vision loss in diabetic patients. Although anti-vascular endothelial growth factor (anti-VEGF) agents are first-line treatments, corticosteroids like dexamethasone (DEX) intravitreal implant have shown potential synergistic effects. This meta-analysis aimed to evaluate the efficacy and safety of DEX intravitreal implant combined with anti-VEGF agents compared to anti-VEGF monotherapy.MethodsA systematic search of PubMed, Embase, Web of Science, Science Direct, Wiley online, and Google scholar was performed up to April 2025. Primary outcomes were changes in best-corrected visual acuity (BCVA) and central macular thickness (CMT). Meta-analyses were performed using Review Manager (RevMan) version 4.4.1.ResultsEight studies comprising a total of 597 eyes were included in this meta-analysis. The pooled analysis demonstrated no statistically significant difference in BCVA between combination therapy and anti-VEGF monotherapy (Mean Difference [MD] = 1.79; 95% Confidence Interval [CI]: -1.68 to 5.26, P = 0.311). However, combination therapy resulted in a significantly greater reduction in CMT compared to anti-VEGF treatment alone (MD = -64.11 μm, 95% CI: -99.69 to -28.53, P < 0.001). The overall risk of bias across studies was rated as low to moderate. However, the incidence of adverse events is significantly higher in the combination therapy group.ConclusionsDEX combined with anti-VEGF agents confers superior anatomical outcomes in reducing CMT compared to anti-VEGF monotherapy in the management of DME. However, further large-scale, multicenter randomized controlled trials with extended follow-up are warranted to validate these findings and optimize treatment protocols.